Gambaran Pengetahuan dan Perilaku Pelayanan Antibiotik Tanpa Resep di Apotek Kota Pasuruan dengan Metode Kuesioner - Dinda Mirza Ayu Maretha (Fakultas Farmasi, 2024)
This study aims to address the escalating issue of antibiotic resistance each year, particularly focusing on the prevalent practices of non-prescription antibiotic services in pharmacies within Pasuruan City, as indicated by previous studies. Consequently, this study was conducted to explore the knowledge of pharmacist, depict the practices of non-prescription antibiotic services, and analyze the factors driving such practices. The research method involved data collection using questionnaires distributed to pharmacist in Pasuruan City. The questionnaire was designed to assess their knowledge about antibiotics, depict the practices of non prescription antibiotic services, and identify influencing factors. The results of the study revealed that the average knowledge of pharmacist in Pasuruan City reached 6.58, indicating a satisfactory level of knowledge. However, 81.25% of pharmacist admitted to having provided non-prescription antibiotic services. The primary factor driving this practice was the belief among pharmacist that patients have adequate understanding of antibiotic use. The antibiotic often dispensed without a prescription is amoxicillin. Nearly all respondents reported having conducted assessments on patients (94.87%) and providing information (92.31%). Common questions during assessments were related to symptoms and duration, while frequently provided information to patients included instructions on drug consumption and the duration of usage
Reaploud Repository February_Hasyim
Keywords: Non-prescription antibiotic services; Pasuruan City pharmacies; Questionnaire